Reflective Hyperconnectivity of Social Networks Virtual Space as a Factor in the Design of Distant Learning Environment - K. A. Melezhik; A. D. Petrenko; D. M. Khrabskova (Высшее образование в России, 2020)
In this article, topics related to the urgent transition to distance education (DE), through decisive measures taken to protect Russian university community against consequences of COVID-19 epidemic are covered. Based on semi-structured interviews with administrators, faculty, IT specialists and students, it is argued that in the force majeure circumstances the university offers for DE a standard model of one-size-fits-all curriculum though modified through information and communication technologies. The use of the Internet in a localized online space is limited to delivering courses without considering needs of individual learners, their autonomy, preferences and prior knowledge of the subject. The observation method was used by both participant and non-participant. An experiment on the teachers’ self-assessment proves that many still view the university as a source of offline information for students. The article purports to discuss ways to promote DE by the concepts of postindustrial educational space connectivism, hyperconnectivity of social networks, teachers’ reflective practice, digital nativity of teachers and students in mastering information and communication technologies. It is claimed that real transition of a Russian university to DE cannot be achieved without internet-provided increased transactional distance in the dialogue between the teacher and students mediated by technology and reflective approach.